The sensitization potential of sunscreen after ablative fractional skin resurfacing using modified human repeated insult patch test - Waranya Boonchai (2018)
© 2015 Informa UK Ltd. Background: Ablative fractional skin resurfacing has become popular and proven to be useful in treating scars, photoaging and wrinkles. Although post-inflammatory hyperpigmentation (PIH) is the most common complication especially in dark-skinned patients like Asian. Several modalities have been used to overcome the PIH. Objective: To determine the sensitization potential of sunscreen applied immediately after ablative fractional skin resurfacing. Material and methods: Sixty volunteers were recruited. Of these 30 subjects were from previous ablative fractional skin resurfacing study who applied broad-spectrum sunscreen containing anti-inflammatory agent starting on the first day after resurfacing and another 30 non-resurfacing subjects had applied the same sunscreen on the intact skin. All subjects were patch/photopatch tested for sensitization study by using modified human repeated insult patch test (HRIPT). Results: There were significantly higher sensitization rate of UV-filter, octocrylene and the sunscreen in resurfacing group than in non-resurfacing group. Conclusion: Early application of sunscreen after ablative fractional skin resurfacing has increased the incidence of sensitization potential of sunscreen. The sunscreen is recommended to start using from D3 after fractional ablative skin resurfacing to ensure the complete recovery of skin barrier and minimize the risk of sensitization.